Host-Related Factors as Targetable Drivers of Immunotherapy Response in Non-Small Cell Lung Cancer Patients - Baci, Denisa; Cekani, Elona; Imperatori, Andrea; Ribatti, Domenico; Mortara, Lorenzo (Frontiers in Immunology, 2022)
Despite some major therapeutic breakthroughs leading to immunotherapy, especially immune checkpoint inhibitors, a high percentage of patients with non-small cell lung cancer (NSCLC) do not respond to treatment on relapse, thus experiencing poor prognosis and survival. The reasons for these unsatisfying results could be related to the features of the tumor immune microenvironment (TIME) and the dynamic interactions between tumor, and immune infiltrate. Host-tumor interactions strongly influence the course of disease and response to therapies. Thus, targeting host-associated factors by restoring their physiologic functions altered by the presence of tumor represents a new therapeutic approach to control tumor development and progression. In NSCLC the tumor immunogenic balance is shifted negatively towards immunosuppression due to the release of inhibitory factors as well as the presence of immunosuppressive cells. Among these cells, there are myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs) that can generate a tumor-permissive milieu by reprogramming cells of the hosts such as tumor-associated macrophages (TAMs), tumor-associated neutrophils (TANs), natural killer (NK) cells, dendritic cells (DCs), and mast cells that acquire tumor-supporting phenotypes and functions. This review highlights the current knowledge of the involvement of host-related factors including, innate and adaptive immunity in orchestrating tumor cell fate and the major mechanisms of resistance to immunotherapy in NSCLC. Finally, we discuss combinational therapeutic strategies targeting different aspects of the TME to prime the host response. Further research dissecting the characteristics and dynamic interactions within the interface host-tumor is necessary to improve patient fitness immune response, provide answers regarding the immunotherapy response, and develop more effective treatments for NSCLC.